MERDEKA BELAJAR MENURUT SUDUT PANDANG KI HADJAR DEWANTARA DALAM PEMBENTUKAN KARAKTER PROFIL PELAJAR PANCASILA PESERTA DIDIK DI SEKOLAH - Arta Jaya, I Kadek; I Made Sukma Muniksu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Humans are creatures that struggle intensely with education. That is why humans are given the nicknames as animal educandum and animal educandus. Humans are human beings who are gifted with reason, so humans need education in the process of their life. The existence of the idea of independent learning is a very good idea where this idea has given educators and students freedom in determining the learning system. In a lesson is determined by the teaching itself. The influence of this teaching generally liberates humans for their lives from birth, while the independence of the inner life comes from education. An independent human being is a human whose life does not depend on other people, but relies on his own strength. Meanwhile, Indonesian students are lifelong students who are competent, have character, and behave according to Pancasila values. In the process of implementing independent learning, of course there will be obstacles and obstacles. This research is a qualitative research that uses a literature study approach by reading various relevant literature in the form of books, journals, newspapers, magazines, the internet, and other important records. While this study aims to describe the independent learning according to Ki Hadjar Dewantara's view in the formation of Pancasila student profiles, describe the supporting and inhibiting factors in the formation of Pancasila student profiles in schools and the solutions sought in learning that takes place in schools in the formation of Pancasila student profiles. Based on the results of the analysis carried out, the results of this study indicate that independent learning is the right step to achieve an ideal education that is in accordance with current conditions and the aim is to prepare students who are strong, intelligent, creative, and have character that is in line with the values Pancasila. In addition, the implementation of independent learning according to Ki Hadjar Dewantara's view is very relevant to the development of Pancasila student profiles, namely students can internalize Pancasila values in their lives and consider aspects of balance of creativity, taste and intention. Meanwhile, the driving factors in the formation of a Pancasila student profile consist of: 1) Inheritance from oneself (internal factors); 2) Personality (internal factors); 3) Family (external factor); 4) Educators (external factors); and 5) Environment (external factors). While the inhibiting factors in the formation of Pancasila student profiles in schools are the lazy character of a small number of students, the limitations of educators in designing good lesson plans or teaching modules, the limitations of educators in using media, IT and various learning resources, and also the lack of time available to teaching and learning activities. Meanwhile, problem solving carried out by educators includes using a psychological approach to students through habituation, role models, examples and moral guidance and mentoring.